Ecotect: as part of the learning experience for young architecture students to raise awareness in environmental responsive building design - Sanusi, Aliyah Nur Zafirah; Denan, Zuraini (2012)
This study investigates the feasibility of introducing environmental analysis software called Ecotect to final year LAM Part 1 Architecture students in the International Islamic University Malaysia (IIUM). The study evaluates the students’ response and perception towards the software after completing the environmental analysis assignment. The assignment was given during the Environmental Conscious Design course and the students were required to conduct natural daylight analysis and average indoor thermal analysis of their studio design project using the Ecotect software. A student feedback survey on the Ecotect assignment was conducted among 64 students. Rather positive feedbacks were obtained from the students. In overall, 72% students were fully satisfied and 22% students were neutral with the Ecotect Assignment. However, 89% of the students agreed for the assignment to remain within the Environmental Conscious Design course since they had benefitted from the exercise. Majority of the students suggested the assignment to be introduced at earlier stage. Based on the high percentage of positive feedbacks from the IIUM architecture students, the teaching and exercise of Ecotect should be extended to more students and a brief introduction of such software to students in the 1st year of LAM Part 1 Architectural Studies could make the learning experience more effective.